PERENCANAAN BENDUNGAN BENER KABUPATEN PURWOREJO - Kusuma Dewi, Claudia Ratna; Lubis, Dwiarta Agustina; Edhisono, Sutarto; Budieny, Hary (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
One of the efforts to develop the potency of Bogowonto River and increase the wellness and the living of the people near the river is by making a Dam.The most advantage for the dam is at Guntur Village, Bener Subdistrict, Purworejo Regency.Â It is planned the dam will be able to irrigate 1800 Ha of existing and 407 Ha of expanded rice field and water demand in eight subdistricts of Purworejo Regency.Â Bener Dam is designed with rock fill dam as its structure. The height of the Dam is 112 meters with slope ratio 1:2.5 at the upper course and 1:2.25 at the lower course for 50 years lifetime and storage capacity 28 million m3.Â